ΔΩΔΕΚΑΝΗΣΟΣ, Η ΓΕΝΕΣΗ ΕΝΟΣ ΟΝΟΜΑΤΟΣ ΚΑΙ Η ΑΝΤΙΜΕΤΩΠΙΣΗ ΤΟΥ ΑΠΟ ΤΟΥΣ ΙΤΑΛΟΥΣ - ΓΙΑΝΝΟΠΟΥΛΟΣ, ΓΙΑΝΝΗΣ (Eoa kai Esperia, 2006)
The islands, the islets, and the rocks of the Dodecanese prefecture unitedwith Greece in 1947. At the 2001 census 15 islands and 93 islets or rocks areregistered. In ancient Greece these were known as (South) Sporades, whereasthe name Dodecanese is known since the 8th century and was used later forthe Cyclades, which in the later ancient era (according to Stravon) actedsimilarly as twelve islands (dodeca nesoi).During the Ottoman domination (1522-1912), twelve of the SouthSporades islands, with the exception of Rhodes and Kos, were widelyprivileged by self government. In the 19th century, when these privileges wereabolished, the inhabitants strived to maintain them. Their representatives in1909, in a memorandum to the Ottoman Porte, named the islands Dodeca(Twelve) South Sporades, using the name Dodecanese for the first time. In1912, when Italy occupied all of the then 12 privileged islands, and afterdistinguishing Lipsus as an island by appointing a government, the islandswere name Rodi e Dodecanese However, the same year, the Greekrepresentatives, at their congress in Patmos in which they declared theirindependence, referred to the islands as the Aegean Islands or as (South)Sporades.Since 1913, when Gerasimos Drakidis a Rhodes lawyer published inAthens the Dodecanese's Album, in which he included the results of the recentréférendums among the inhabitants of the twelve islands (Rhodes, Chalki,Symi, Telos, Astypalea, Nissyros, Kos, Kalymnos, Leros, Patmos, Kassos, Karpathos),in favour of the unification with Greece, which had taken placeduring the First Balkan War, the name Dodecanese prevailed immediatelyboth in oral and written communication/speech, in Greece and abroad.Soon, when the Italians comprehended that the predominance of theGreek name was against their interests, they reacted in two ways. On the onehand, some clamed that the name was of Italian inspiration and was chosen asbeing of classical or medieval origins, trying to declare their claims in theMediterranean as a movement to promote the new roman / latin civilization, a nuova romanità / latinità. On the other, some supported the weak argumentthat the islands were 14 and not 12, so they could not be named (dodeca = 12)Dodecanese. The 12 mentioned above, initially included Lipsus and later asecond one, Kastellorizo whose rights were conveyed to Italy by France in1921. During the domination of fascism in Italy in 1922 and Turkey'sabdication in 1923 (Lausanne Treaty), a policy for the unification anditalianisation of the Greek population was adopted, and in 1930 the islandswere named by decree Isole Italiane dell'Egeo.Due to the Italian Armistice in 1943, during the Second World War (1939-1945), and after the signing of the Paris Treaty in 1947, according to which theislands were handled over to Greece, the name which since 1913 had prevailedbecame the official name of the islands. All these islands constituted what wascalled the "Dodecanese general administration" and later, in 1955, theDodecanese prefecture was established.